2016
DOI: 10.1016/j.neuron.2016.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Enhances Social Recognition by Modulating Cortical Control of Early Olfactory Processing

Abstract: SUMMARY Oxytocin promotes social interactions and recognition of conspecifics that rely on olfaction in most species. The circuit mechanisms through which oxytocin modifies olfactory processing are incompletely understood. Here, we observed that optogenetically induced oxytocin release enhanced olfactory exploration and same-sex recognition of adult rats. Consistent with oxytocin’s function in the anterior olfactory cortex, particularly in social cue processing, region-selective receptor deletion impaired soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
276
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(286 citation statements)
references
References 93 publications
(118 reference statements)
10
276
0
Order By: Relevance
“…In further support of the social specificity of these findings, mice with a conditional knockout of oxytocin receptors in the AON were impaired in a social recognition test. This impairment did not reflect reduced initial interaction, demonstrating that, in social contexts, oxytocin receptors in the AON must be activated to enhance early olfactory responses to socially relevant cues (Oettl et al, 2016).…”
Section: Oxytocin Enhances the Salience Of Socially Relevant Sensorymentioning
confidence: 84%
See 1 more Smart Citation
“…In further support of the social specificity of these findings, mice with a conditional knockout of oxytocin receptors in the AON were impaired in a social recognition test. This impairment did not reflect reduced initial interaction, demonstrating that, in social contexts, oxytocin receptors in the AON must be activated to enhance early olfactory responses to socially relevant cues (Oettl et al, 2016).…”
Section: Oxytocin Enhances the Salience Of Socially Relevant Sensorymentioning
confidence: 84%
“…In a same-sex social interaction test, known to be oxytocin dependent, optogenetic activation of oxytocin neurons in the PVN lead to a significant increase in social exploration between female rats resulting in enhanced memory, with rats showing differential exploration of a novel versus familiar partner even after a 2-hour interval, by which time control rats' exploration was at chance levels (Oettl et al 2016). This effect of oxytocin was socially specific as there was no effect on object recognition.…”
Section: Oxytocin Enhances the Salience Of Socially Relevant Sensorymentioning
confidence: 95%
“…The VTA also modulates pair bonding in male prairie voles (Curtis and Wang, 2005); projects to, releases dopamine (DA) within, and modulates IEG expression in multiple SSN nuclei (Argiolas and Melis, 2013); and contains OTR-expressing neurons that modulate both social behavior and dopamine release into the NAc shell (Peris et al, 2016; Shahrokh et al, 2010; Song et al, 2016; Stivers et al, 1988). The AON and MeA were selected due to their role in OTR-dependent social odor processing and social recognition (Ferguson et al, 2001; Gur et al, 2014; Oettl et al, 2016; Wacker and Ludwig, 2012). Direct projections from the BLA modulate both cue-evoked excitation of accumbal neurons and reward-seeking behavior; and this circuit is thought to relay sociosensory information from the amygdala to the NAc shell during formation of selective social attachments (Ambroggi et al, 2008; Numan and Young, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the SSN is a neural network that is hypothesized to modulate selective social attachment and other forms of associative social learning by attaching valence and incentive salience to sociosensory cues. The SSN includes multiple SDMN nodes as well as multiple non-SDMN nodes, including the anterior olfactory nucleus (AON) and prefrontal cortex (PFC)—where OTR activation is critical for social learning and behavior in rodents (Nakajima et al, 2014; Oettl et al, 2016; Young et al, 2001)—and the paraventricular nucleus of the hypothalamus (PVN), a primary site of OT synthesis. We previously found that endogenous central OTR signaling during sociosexual interaction does not strongly modulate levels of Fos-immunoreactivity (Fos-ir) within individual SSN nuclei, but strongly modulates patterns of correlated Fos-ir across SSN nuclei, consistent with hypotheses that central OTRs modulate distributed neural network activity during social contexts (Johnson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A key mechanism by which oxytocin affects social signaling may be by modulating the excitatory/inhibitory balance in this circuit (2). Oxytocin enhances top-down signals to olfactory bulb interneurons, thereby increasing overall inhibitory tone and improving signal-to-noise ratio for olfactory signaling of social information (2,3). This activity is important for both learning and recall of social information.…”
mentioning
confidence: 99%